Spider Silk Inspired Robust and Photoluminescent Soybean‐Protein‐Based Materials. Issue 8 (14th May 2021) - Zhou, Ying; Dong, Youming; Li, Xiaona; Li, Jiongjiong; Shi, Sheldon Q.; Li, Jianzhang; Luo, Jing
Abstract: Development of mechanical robust and functional biomass‐based materials still remains challenging. Here, a design strategy inspired by spider silk structure is proposed to prepare strong, robust, and photoluminescent soybean protein isolate (SPI)‐based materials, by integrating epoxy soybean oil (ESO) and SPI as soft phase matrices and graphene oxide quantum dots (GQDs) as hard phase. The results show that the soft–hard coordination network can form a close covalent/hydrogen bond network. The tensile strength, elongation at break, and toughness of the SPI/ESO/GQD film are 13.22 MPa, 209%, and 22.54 MJ m −3, respectively. In addition, SPI/ESO/GQD has strong photoluminescence intensity due to the ring‐opening polymerization of amino structure with epoxy resin. The prepared SPI‐based materials are promising candidates for optical coatings and provide new ideas for the intelligent research of other protein‐based materials. Abstract : The design strategy inspired by spider silk is used to prepare strong and luminous soybean protein isolate (SPI)‐based materials. The tensile strength, elongation at break, and toughness of the film are 13.22 MPa, 209%, and 22.54 MJ m −3, respectively, and it has a strong photoluminescence intensity. The prepared SPI‐based film is a promising material.